Vision : the approach of biophysics and neurosciences : proceedings of the International School of Biophysics, Casamicciola, Napoli, Italy, 11-16 October 1999 - Musio, Carlo (Series on biophysics and biocybernetics ;, 2001)
The light sense is conceivably the key sense in both the animal and the plant kingdom. Vision research, undoubtedly a fast-growing field, is providing impressive results - thanks to modern theoretical and methodological advances. The approach of biophysics and neuroscience seems to be of great benefit and, for this reason, the present book gives an outline of recent acquisitions and updated advanced methods concerning this approach. Visual mechanisms and processes are analysed at several (molecular, cellular, integrative, computational and cognitive) levels by different methodologies (from molecular biology to computation) applied to different living models (from protists to humans, via invertebrates and lower vertebrates).